Business opportunities in the Julio Andrade parish, canton Tulcan, province of Carchi - Pérez Quiroz, Roberth Patricio; Enríquez Carapaz, Estefany Elizabeth; Collaguazo Collaguazo, Nathaly Joselyn (Tierra Infinita, 2022)
Julio Andrade is the most populated parish in the rural sector of the Tulcán canton and stands out for dedicating itself to agriculture and livestock; The poor creation of new business opportunities within the sector has led to 80% of the economically active population of the parish currently dedicating themselves to these economic activities, following the customs of parents and grandparents. The purpose of the study is to identify the main business opportunities that can be developed within the parish, as well as the analysis of determining aspects for the identification of new business opportunities according to the characterization and current reality of the study area. A quantitative methodology was used with a descriptive and documentary research design, for the data collection process the application of two instruments, a survey and a structured interview, was carried out. With the analysis carried out from the information and data collected, it is identified that the parish of Julio Andrade has a valuable potential in resources mainly within the agricultural sector, the production of potatoes, milk and peas is important and given this reality they can be developed new strategies for generating income and improving the economy of the area and its population. Finally, conclusions and recommendations are presented that are left for consideration as important alternatives for the generation of business ideas that, associated with a set of skills, capacities and knowledge of internal and external entrepreneurs, will be able to enhance the business vision of local development.
Keywords: business opportunities; entrepreneur; local development